Implementasi Pengelolaan Bantuan Keuangan Umum dan Khusus Kepada Desa Berdasarkan Peraturan Bupati No. 24 Tahun 2023 di Desa Kletek, Kec. Taman, Kab. Sidoarjo - Dicky Satria Ananta Haqq; Maulidah Narastri (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study examines the implementation of general and special financial assistance management in Kletek Village, Taman District, Sidoarjo Regency, including Village Funds (DD), Village Fund Allocations (ADD), revenue sharing from regional taxes and levies, and Frontage Road construction compensation as regulated under Regent Regulation No. 24 of 2023. A descriptive qualitative approach was employed, with data collected through in-depth interviews, observation, and documentation. The findings show that general financial assistance has been managed effectively through participatory planning mechanisms such as Village Consultative Meetings and Village Development Planning Meetings, which form the basis for preparing the Village Budget (APBDes). Village Funds are mainly allocated to physical development, while ADD supports governance and limited development activities. Revenue sharing from taxes and levies helps address the village’s limited original income. Special financial assistance is integrated into village development plans through spatial adjustments and infrastructure improvements. Supporting factors include coordination among village officials, community participation, and clear regulations, while challenges include limited local revenue and uneven public understanding.